Девиация как композиционная стратегия лирического текста: Заметки о поэзии Георгия Иванова - Zel’dovich, Gennadii (Wiener Slawistischer Almanach, 2023)
The paper is devoted to the role of linguistic and/or logical deviations in lyrical texts. It is shown that the former ones can be one of the driving forces propelling the development of the poem, in the sense that it may open with a deviation, while its later fragments are at least partly built as a series of attempts at its adjustment, their eventual success being the signal of completion of the text. It is argued also that such a compositional strategy assists in marking foreground-background distinctions in lyrical poems.